Navicula watveae sp. nov. (Bacillariophyceae) a new diatom species from the Western Ghats, India - Radhakrishnan, Cheran; Pardhi, Samadhan; Kulikovskiy, Maxim; Kociolek, J. Patrick; Karthick, Balasubramanian (Phytotaxa, 2020)
A new species of Navicula sensu stricto is described from a small stream from the Kaas Plateau in the northern part of the Western Ghats of India. The species is presented with light and scanning electron microscopy, and compared with similar species like Navicula reinhardtii, N sovereignii, N. aurora and N. gogorevii. This taxon is characterized by rhomboid shape, elongated lineolae, short striae at the central area giving a distinctive shape, and narrowly-rounded apices. The discovery of this taxon signifies that a significant number of species to be discovered in this biodiverse region of peninsular India, especially unique habitats like lateritic plateaus.